Community Empowerment in Reducing Waste Cooking Oil into Eco-Friendly Soap Products - Dian Puspita Anggraini; Devita Sulistiana (Institut Agama Islam Negeri Ponorogo, 2024)
The community service program, located in Sukosewu Hamlet, Sukosewu Village, Gandusari District, Blitar Regency, aims to address the issue of used cooking oil waste, reduce environmental pollution caused by used cooking oil, and diversify processed products from the PKK group. The implementation method of this service activity includes outreach/socialization and assistance to the PKK group, conducted over a two-month period. The socialization method was carried out in Sukosewu Hamlet in May-June 2024 to convey the purpose and objectives of this service program by providing theoretical information on the procedures and mechanisms for processing used cooking oil into eco-friendly soap. The assistance activity involved direct guidance, resulting in the creation of a new product, eco-friendly soap, which can increase the community's economic value (income). Additionally, PKK participants gained a deeper understanding and awareness of the dangers of used cooking oil to human health and the environment as a result of this outreach and training. Ultimately, participants also learned how to properly dispose of used cooking oil waste and utilize it to prevent environmental pollution.